2015
DOI: 10.1530/erc-15-0442
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a heritable contribution to neuroendocrine tumors of the small intestine

Abstract: Small intestine neuroendocrine tumors (SI-NETs) are rare tumors arising from the enterochromaffin cells of the gut. Having a first-degree relative with a SI-NET has been shown to confer a substantial risk arising from shared environment and genetics. Heritable risk was examined using a computerized genealogy linked to historical statewide cancer data. A population-based analysis of the observed familial clustering of SI-NETs was performed to assess the genetic risk in distant relatives. A test for significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…These cells contain a large amount of our body storage of serotonin. Clear information about how these tumors develop is limited ( 68 ), but recent studies tried to shed light on the genomic landscape of SI-NETs. Banck and colleagues have first analyzed 48 SI-NETs by massive parallel exome sequencing, both in tumors and in their normal tissue counterpart.…”
Section: Hereditary Syndromesmentioning
confidence: 99%
“…These cells contain a large amount of our body storage of serotonin. Clear information about how these tumors develop is limited ( 68 ), but recent studies tried to shed light on the genomic landscape of SI-NETs. Banck and colleagues have first analyzed 48 SI-NETs by massive parallel exome sequencing, both in tumors and in their normal tissue counterpart.…”
Section: Hereditary Syndromesmentioning
confidence: 99%
“…Small intestinal NETs (SI-NETs) have also been described to occur with familial aggregation in a small fraction of patients (133,134). Despite substantial efforts no definitive genetic basis for this phenomenon has been described.…”
Section: Small Intestinal Netsmentioning
confidence: 99%
“…Notably, epidemiological studies have demonstrated that non-syndromic individuals with an affected relative are at an increased risk of developing gastroenteropancreatic (GEP) NENs. In individuals with affected siblings, the relative risk of GEP NEN increases by 13.4-fold, and an increased risk (2.3-fold) is present even in third-degree relatives ( Neklason et al . 2016 ).…”
Section: Dear Editormentioning
confidence: 99%